2018
DOI: 10.3389/fmed.2018.00106
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imaging in Diagnosing Axial Spondyloarthritis

Abstract: Imaging has a central role in the diagnosis, management, and follow-up of patients with axial spondyloarthritis (axSpA). For the early diagnosis of axSpA, magnetic resonance imaging is of utmost relevance. While no novel imaging techniques were developed during the past decade, improvements to the existing modalities have been introduced. This report provides an overview of the applications and limitations of the existing imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 115 publications
(144 reference statements)
0
33
0
Order By: Relevance
“…These changes, which are seen in more advanced disease, are not readily imaged using other techniques such as ultrasound, which cannot penetrate the bone surface [ 25 ]. However, plain radiography has limited utility in assessing the early soft-tissue changes seen in PsA [ 13 , 26 ], especially axial changes [ 27 ]. Radiographs taken during this stage of the disease can appear normal, resulting in a significant delay in diagnosis if other imaging modalities are not used.…”
Section: Introductionmentioning
confidence: 99%
“…These changes, which are seen in more advanced disease, are not readily imaged using other techniques such as ultrasound, which cannot penetrate the bone surface [ 25 ]. However, plain radiography has limited utility in assessing the early soft-tissue changes seen in PsA [ 13 , 26 ], especially axial changes [ 27 ]. Radiographs taken during this stage of the disease can appear normal, resulting in a significant delay in diagnosis if other imaging modalities are not used.…”
Section: Introductionmentioning
confidence: 99%
“…Radiography only detects changes at a relatively late stage of disease, such as periosteal bony apposition or bony erosions, and is inferior to MRI in the evaluation of the disease extent and severity ( 63 , 64 ). Scintigraphy has been widely used in the past; however, due to its lack of specificity it has been replaced by MRI and ultrasound (US) ( 65 , 66 ). Despite providing interesting preliminary results ( 67 , 68 ), positron emission tomography (PET) does seem neither specific nor able to offer the same excellent spatial resolution as MRI, requiring further research in this field.…”
Section: Imaging To Differentiate Spa From Fmmentioning
confidence: 99%
“…Kamanli et al and Said-Nahal et al found higher frequency of HLA-B*35 in HLA-B*27 negative SpA patients [24,25] and genetic research on ancient human remains showed an association of HLA-B*40, HLA-B*27 and HLA-B*35 alleles in individuals with rheumatic diseases, particular in individuals with SpA [26]. This association is based on studies in which sacroiliitis was detected by conventional X-ray but the structural lesions visible on X-ray are a sign of advanced disease and therefore diagnosing with X-rays may delay diagnosis of SpA for seven years [27]. Apart from its inability to detect early sacroilliitis, there is also significant observer variation in reading radiographs of sacroiliac (SI) joints [28].…”
Section: Introductionmentioning
confidence: 99%